Biomimetic porous Mg with tunable mechanical properties and biodegradation rates for bone regeneration - Kang, Min-Ho (2020)
The medical applications of porous Mg scaffolds are limited owing to its rapid corrosion, which dramatically decreases the mechanical strength of the scaffold. Mimicking the bone structure and composition can improve the mechanical and biological properties of porous Mg scaffolds. The Mg structure can also be coated with HA by an aqueous precipitation coating method to enhance both the corrosion resistance and the biocompatibility. However, due to the brittleness of HA coating layer, cracks tend to form in the HA coating layer, which may influence the corrosion and biological functionality of the scaffold. Consequently, in this study, hybrid poly(ether imide) (PEI)-SiO2 layers were applied to the HA-coated biomimetic porous Mg to impart the structure with the high corrosion resistance associated with PEI and excellent bioactivity with SiO2. The porosity of the Mg was controlled by adjusting the concentration of the sodium chloride (NaCl) particles used in the fabrication via the space-holder method. The mechanical measurements showed that the compressive strength and stiffness of the biomimetic porous Mg increased as the portion of the dense region increased. In addition, following results show that HA/(PEI-SiO2) hybrid-coated biomimetic Mg is a promising biodegradable scaffold for orthopedic applications. In-vitro testing revealed that the proposed hybrid coating reduced the degradation rate and facilitated osteoblast spreading compared to HA- and HA/PEI-coating scaffolds. Moreover, in-vivo testing with a rabbit femoropatellar groove model showed improved tissue formation, reduced corrosion and degradation, and improved bone formation on the scaffold. STATEMENT OF SIGNIFICANCE: Porous Mg is a promising biodegradable scaffold for orthopedic applications. However, there are limitations in applying porous Mg for an orthopedic biomaterial due to its poor mechanical properties and susceptibility to rapid corrosion. Here, we strategically designed the structure and coating layer of porous Mg to overcome these limitations. First, porous Mg was fabricated by mimicking the bone structure which has a combined structure of dense and porous regions, thus resulting in an enhancement of mechanical properties. Furthermore, the biomimetic porous Mg was coated with HA/(PEI-SiO2) hybrid layer to improve both corrosion resistance and biocompatibility. As the final outcome, with tunable mechanical and biodegradable properties, HA/(PEI-SiO2)-coated biomimetic porous Mg could be a promising candidate material for load-bearing orthopedic applications.